2022
DOI: 10.3389/fcvm.2022.837584
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Right Ventricular Strains Using Novel Three-Dimensional Analytical Software in Patients With Cardiac Disease

Abstract: BackgroundRight ventricular (RV) three-dimensional (3D) strains can be measured using novel 3D RV analytical software (ReVISION). Our objective was to investigate the prognostic value of RV 3D strains.MethodsWe retrospectively selected patients who underwent both 3D echocardiography (3DE) and cardiac magnetic resonance from January 2014 to October 2020. 3DE datasets were analyzed with 3D speckle tracking software and the ReVISION software. The primary end point was a composite of cardiac events, including card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The mean (±SD) age of the patient population was 63±15 years, 46% were females, and the follow-up duration ranged from 3 to 44 months. Three studies included patients with pulmonary hypertension exclusively (14, 16, 20), one included patients with COVID-19 only (23), one included patients with dilated cardiomyopathy only (22), one included patients with aortic stenosis only (18), one included heart failure patients with preserved left ventricular (LV) EF (HFpEF) only (19), and the remaining three studies included populations with a mixture of cardiovascular diseases (12, 17, 21).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean (±SD) age of the patient population was 63±15 years, 46% were females, and the follow-up duration ranged from 3 to 44 months. Three studies included patients with pulmonary hypertension exclusively (14, 16, 20), one included patients with COVID-19 only (23), one included patients with dilated cardiomyopathy only (22), one included patients with aortic stenosis only (18), one included heart failure patients with preserved left ventricular (LV) EF (HFpEF) only (19), and the remaining three studies included populations with a mixture of cardiovascular diseases (12, 17, 21).…”
Section: Resultsmentioning
confidence: 99%
“…In three instances (including 3-3 studies), there was an apparent overlap between the patient cohorts; 9,13-17 therefore, studies with a higher number of participants were included. 13,15,17 Overall, ten 13,15,[17][18][19][20][21][22][23][24] independent studies were included in the final quantitative analysis (Figure 1), which reported the impact of unit change of RVEF and TAPSE (n=8), 13,16,18,[20][21][22][23][24] or FAC (n=7), 13,[19][20][21][22][23][24] or FWLS (n=7), 17,[19][20][21][22][23][24] on clinical outcomes (all-cause mortality and/or cardiopulmonary adverse events) as HRs. Four studies were prospective, while six were retrospective.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal strain (LS) of the left (LV) and right ventricles (RV) is a well-established biomarker of ventricular dysfunction, having a robust predictive power to future adverse outcomes in numerous cardiac diseases ( 1 , 2 ). In contrast to ejection fraction (EF), a global measure of pump function, LS enables the quantification of ventricular deformation along their long axis.…”
Section: Introductionmentioning
confidence: 99%